Relationship Between Parents Surveilance, Intensity of Peer Group Communication, and Self Esteem To Preferences Play Online Games on Adoloescents - Sharon Gracia G; Djoko Setyabudi, S.Sos, MM (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Online gaming already not become familiar to our ears. However, his presence is still keenly felt, and also in demand by children - teen age children. Internet cafes based online games have been one of the proofs that the online game market has not subsided and is still much demand. Many teenagers, especially boys who like to play this game. And an attraction for researchers to conduct research on this. Playing online games can be affected by family background, playmates (peer group), as well as coming from himself.This quantitative research aims to explain that the family, peer group, and self -esteem have a stake in online gaming. As for those who were respondents in this study were male junior high school age, 12-15 years of online gaming. Based on the theory of parental mediation by Livingstone and Hesper, peer group by Santrock concept, and the concept of self-esteem by Coopersmith, we can see if these three variables as indicators of son preference in playing the game online. The sampling technique used was accidental sampling of 30 respondents men - men aged 12-15 years and the status of junior high school students.Results of studies using Kendall correlation is that first, there’s no positive relationship between the variables of the parents surveilance thru play online games on adolescents. It looks of figures a significance of 0.903 (0.903> 0.05) and a correlation coefficient of 0.020 indicates that the first hypothesis researchers that there is a positive relationship between the parents surveilance to preferences play online games on adolescents denied. The second variable is the intensity of the peer group and the communication of research results, there is a positive relationship as seen in the figure of significance of 0.009 (<0.05) with a correlation coefficient of 0.421 indicates that the second hypothesis the researchers accepted that there is a positive correlation between the intensity of peer communications group to preferences play online games on adolescents. The third variable in this study is self-esteem. The results showed that there is a positive relationship. This looks at the significance of the figure of 0.009 (<0.05) with the number correlation coefficient of 0.417, this shows the third hypothesis the researchers accepted that there is a positive relationship self-esteem to preferences play online games on adolescents.From the results of research states that the theory of parental mediation is not the only that determining factors of preference, while the concept of a peer group are factors that affect a person's preference, as well with the theory of self-esteem which also are factors that affect a person's preference